PREPARING CASH FLOW REALIZATION BASED ON MICROSOFT EXCEL USING PIVOT TABLE AS A DATA SORTING TOOL AT PT PERKEBUNAN NUSANTARA I KOTA LANGSA - Cici Astuti; Faisal; Nurul Mawaddah (PT. Radja Intercontinental Publishing, 2024)
This research was conducted at PT Perkebunan Nusantara I, Langsa City. PTPNI is a state-owned company engaged in oil palm and rubber plantations. In preparing financial performance projections for the next period, companies have difficulty obtaining detailed cash flow realization data. This research aims to create detailed data on monthly cash flow realization reports as material for preparing financial performance projections. The data used to compile cash flow realization is data from the export of cash journal data from the SAP application. The result of the research is the formation of a report on the realization of the company's cash flow complete with details that have been sorted using a tool, namely the Pivot Table feature in Microsoft Excel. Keywords— Include 5 – 6.